Case report: A suspected case of chronic pulmonary sparganosis characterized by migrating cavities and tunnel sign - Niu, Zhongfeng; Chen, Lujiao; Zhang, Yanhua; Zhao, Li (Frontiers in Medicine, 2024)
A 20-year-old male patient with a 15-month history of recurrent cough and hemoptysis presented at our hospital with suspected pulmonary sparganosis. Computed Tomography (CT) revealed migratory and variable lesions ranging from patchy shadows to nodular and cavernous foci. Additionally, the location and morphology of the cavities changed rapidly. The patient's peripheral blood eosinophil count remained within the normal range throughout the course of the infection, and antibiotics (moxifloxacin) alleviated the symptoms. At the early stage of admission, there was a slight increase in neutrophil and basophil counts. Initial treatment with a standard dose of praziquantel led to a significant improvement in symptoms, but the symptoms soon relapsed. However, doubling the dose four months later eventually cured the disease. The migratory nature of the CT lesion and the presence of tunnel signs were key to diagnosing a parasitic infection. The variability and rapid changes in the lesion further facilitated the differentiation of the disease, which rarely manifests as a granulomatous cavity.